68.2: Study of Optimized Design for High Resistance Black Matrix at In‐cell Touch Structure. Issue 1 (June 2015) - Na, Younsung; Park, Chul Ho; Kang, Dongwoo; Choi, Youngseok; Jeon, Suho
Abstract : In‐cell touch structure requires a high resistance BM (black matrix) because of touch performance. The high resistance BM must have at least 10 13 Ω cm and there should be little variation by thermal stress. In this study, we analyzed BM electric properties variation by thermal stress in post bake.